Segmented CT pelvis scans with annotated anatomical landmarks - Connolly, Bryan; Wang, Chunliang (AIDA Data Hub, 2019)
5 bone segmentation masks and 15 annotations of anatomical landmarks for pelvis bones in each of 90 Computed Tomography (CT) cases extracted from the [CT Lymph nodes](https://wiki.cancerimagingarchive.net/display/Public/CT+Lymph+Nodes) and [CT Colonography](https://wiki.cancerimagingarchive.net/display/Public/CT+COLONOGRAPHY) collections from the [The Cancer Imaging Archive](https://www.cancerimagingarchive.net/) (TCIA).
Keywords: Radiology; Annotated; Pelvis; CT; Computed tomography; Anatomical landmarks; Bone segmentation; Medical and Health Sciences; Medicin och hälsovetenskap; Radiology and Medical Imaging; Radiologi och bildbehandling